2010
DOI: 10.3109/10428194.2010.483749
|View full text |Cite
|
Sign up to set email alerts
|

High levels of topoisomerase IIα protein expression in diffuse large B-cell lymphoma are associated with high proliferation, germinal center immunophenotype, and response to treatment

Abstract: Gene copy number and protein expression of topoisomerase IIalpha were correlated to benefit from anthracyclines in various tumors. A retrospective series of 69 patients with DLBCL managed with CHOP chemotherapy were studied for immunohistochemical TopoIIalpha expression and numerical gene abnormalities by fluorescent in situ hybridization (FISH). The results were analyzed in relation to the expression of cell cycle proteins (Ki67, p53, HDM2, p21, p14, pRb, p16, and cyclins A, B1, D1, D2, D3, and E) and BCL6/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
3
20
0
2
Order By: Relevance
“…Despite the wealth of studies in this field, none of the proposed mechanisms of resistance to TOPO2 inhibitors is currently considered reliable enough to be exploited on the clinical ground. In fact, although several reports have supported the use of TOPO2 expression levels to select patients more likely to respond to TOPO2 inhibitors [66][67][68][69], a very recent meta-analysis appears to temper the enthusiasms and overall discourages from using this approach for treatment personalization [70]. In addition, no efflux pump inhibitor is currently considered a standard companion of TOPO2 poisons in any chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the wealth of studies in this field, none of the proposed mechanisms of resistance to TOPO2 inhibitors is currently considered reliable enough to be exploited on the clinical ground. In fact, although several reports have supported the use of TOPO2 expression levels to select patients more likely to respond to TOPO2 inhibitors [66][67][68][69], a very recent meta-analysis appears to temper the enthusiasms and overall discourages from using this approach for treatment personalization [70]. In addition, no efflux pump inhibitor is currently considered a standard companion of TOPO2 poisons in any chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 92%
“…Overexpression of Topo IIα indicates a high level of proliferation in neoplastic cells (Pentheroudakis et al, 2010). We have previously demonstrated that an increase in Topo IIα + cells indicates cell proliferation following treatment with renal carcinogens (Taniai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…QAP1 (quinoline aminopurine 1) is an ATP-competitive hTopoII inhibitor which is shown to target both TopoIIα and β isoforms [26]. TopoIIα has been thought to be the main target of topoisomerase poisons like etoposide and doxorubicin, however there is also evidence suggesting that etoposide induced DNA sequence rearrangements and double strand breaks are TopoIIβ dependent [27,28]. NK314, a topoisomerase II poison has been described to be TopoIIα specific agent with in vitro activity against non-small cell cancer, colorectal cancer and human cervical cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%